Los proyectos pedagógicos integradores de áreas, como estrategia para la interdisciplinariedad (2019)
The article addresses the role of the Pedagogic Projects Integrating Areas PPIA of Degree in Basic Education, with emphasis on Mathematics, Humanities and Spanish Language of the Faculty of Distance Studies, in this sense, it presents an approximation about the concept of interdisciplinarity from different authors; at the same time, it describes the PPIAs that are currently working on the program, its importance and their training teachers. Finally, it reflects about PPIA as a pedago- gical and dynamic strategy that allows to have a real vision from the educational for the integral development of the professional and privilege the analytical and critical perception of the needs of their sourronding.